A nano-catalytic approach for C–B bond formation reactions. Issue 6 (30th January 2018) - Verma, Piyush Kumar; Shegavi, Mahadev L.; Bose, Shubhankar Kumar; Geetharani, K.
Abstract : Nanoparticle-catalysed borylation is one of the most convenient methods for the synthesis of organoboranes to overcome the confines of homogeneous catalysis such as recyclability and heavy metal contamination. Abstract : Herein, we present a chronological survey of the metal/metal oxide nanoparticle-catalysed borylation reactions. Transition metal-catalysed borylation is considered to be one of the most efficient methods for the synthesis of organoboron derivatives. Considering chemical and pharmaceutical processes, the major drawbacks of homogeneous catalysis are metal contamination in products and inability to recover catalysts for reuse, which limit its application industrially, in biomolecules, and materials science. The use of nanoparticles as heterogeneous catalysts is a current topic of research to overcome these limitations. This review gives an overview of the metal nanoparticle-catalysed borylation reactions and also discusses the reaction mechanisms.